Holbein's Sir Thomas More - Mantel, Hilary 1952-2022; Salomon, Xavier F. 1979- (Frick diptych series, 2018)
The Frick diptych series begins with the portrait of the humanist scholar Thomas More by the Renaissance painter Hans Holbein. This portrait of the "man for all seasons" is illuminated by Peter Jay Sharp Chief Curator Xavier F. Salomon, who looks anew at both sitter and artist and their remarkable relationship, offering a thorough consideration of this much-praised likeness, its historical context, and its arrival at the Frick. The essay is paired with a piece by the historical novelist Hilary Mantel, whose contribution takes the form of a letter. The form is particularly apt-in some ways Holbein's career in England began with a letter, his letter of introduction from Erasmus, whom he had also painted